Interpretasi Struktur Bawah Permukaan Daerah Gunung Merbabu – Merapi Berdasarkan Pemodelan 3D Anomali Bouguer - Sarkowi, Muh (BERKALA FISIKA, 2010)
Mount Merbabu represent the volcano which keep a lot of mystery because its activity not many known by vulcanology expert. At least existing data about activity of Mount Merbabu cause the its activity characteristic not yet can be expressed surely. Study [of] about characteristic of Mount Merbabu needed to to learn the nature of vulcanisme activity so that action prevetive fall the victim and disaster mitigation can be done early possible. While the Mount of Merapi represent the most active volcano in the world. In Its activity, eruption Merapi Mount yield the hot cloud (wedus gembel) with the temperature 3000 º C to glide the mean reach the distance 4-5 km. In this research we have been done modeling and interpretation of Bouguer anomaly around Mt. Merapi and Merbabu. Result of research indicate that Mt. Merapi and Merbabu have the negative anomaly which because of existence magma chamber. The magma chamber in Mt. Merapi have a convex form with the deepnes from 500 – 6000 meter from meas sea level, while the magma chamber in Mt. Merbabu have the same from but rather minimize with the deppnes magma chamber about 1000 – 4000 meter from means sea level. Magma chamber in Mt. Merapi caontain liquid magma while the solid magma in Mt. Merbabu. Keywords : Mount Merapi, Mount Merbabu, Gravity